Cardiac Drug Therapy - Khan, M. Gabriel (Contemporary Cardiology, 2007)
Cardiac Drug Therapy, 7th ed., addresses the pharmacology and therapeutic application of drugs used to treat heart diseases and hypertension. Additions and updates to the sixth edition include six new chapters on current controversies in cardiac drug therapy such as the beta blocker issue many cardiologists are presently grappling with. The book provides practical advice on how to manage cardiac diseases and addresses the choice of one particular cardiac agent vs. another. In addition to providing core knowledge in cardiovascular therapeutics, the text assists in resolving some of the issues surrounding cardiac drugs. Cardiac Drug Therapy provides practical information including properties, dosage, side effects, potential salutary benefits, and drawbacks on virtually all commercially available cardiac drugs. The text is succinct and straightforward, and highlighted throughout with bullet points that enable rapid-retrieval of clinically relevant information.